2021
DOI: 10.1111/clr.13860
|View full text |Cite
|
Sign up to set email alerts
|

Does the timing of implant placement and loading influence biological outcomes of implant‐supported multiple‐unit fixed dental prosthesis—A systematic review with meta‐analyses

Abstract: Objective To investigate the impact of timing of implant placement and loading on implant survival and biological outcomes of multiple‐unit implant‐supported fixed dental prosthesis (FDPs). Material and Methods A literature search was performed by three independent reviewers for studies reporting on ≥10 patients with FPDs supported by ≥two implants over ≥3 years of follow‐up. Data were analyzed on implant survival and biological complications as primary outcomes and biological events, including changes in peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The contemporary treatment and fabrication concepts aim to minimize therapy durations and medical visits while maintaining optimum clinical and patient-related outcomes of therapy [ 20 ]. Immediate loading therapeutic schedule offer an attractive solution for both clinicians and patients by reducing overall implant treatment time [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The contemporary treatment and fabrication concepts aim to minimize therapy durations and medical visits while maintaining optimum clinical and patient-related outcomes of therapy [ 20 ]. Immediate loading therapeutic schedule offer an attractive solution for both clinicians and patients by reducing overall implant treatment time [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors 12,40,48,51 have similarly concluded no significant difference in dental implant survival rates between general preimplantation and post-implantation RTX. However, there is controversy on the sturdiness of these claims, with some studies showing a slight advantage to implants placed after RTX, 52 with certain authors emphasizing the importance of enough time after the completion of treatment, 53,54 while others found no significant differences 49,55 regarding time after RTX completion. The concept of the optimal implant placement window has been described as at least 6 months after the completion of RTX but within 18 to 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…The implant placement and loading protocols for this systematic review (Aiquel et al, 2021) were adopted as proposed by Gallucci et al, 2018and Siebers et al, 2010(Gallucci et al, 2018and Siebers et al, 2010.…”
Section: Focused Questionmentioning
confidence: 99%
“…The implant placement and loading protocols for this systematic review (Aiquel et al, 2021) were adopted as proposed by Gallucci et al, 2018 and Siebers et al, 2010 (Gallucci et al, 2018 and Siebers et al, 2010). Immediate implant placement (IP): Dental implants are placed in the fresh socket on the same day of tooth extraction. Early implant placement (EP): Dental implants are placed with soft tissue healing or with partial bone healing, 4–8 weeks or 12–16 weeks after tooth extraction. Late implant placement (DP): Dental implants are placed after complete bone healing, more than 6 months after tooth extraction. Immediate loading (IL): Dental implants are connected to the prosthesis within 1 week subsequent to implant placement. Early loading (EL): Dental implants are connected to the prosthesis between 1 week and 2 months after implant placement. Conventional loading (DL): Dental implants are allowed a healing period more than 2 months after implant placement with no connection to the prosthesis. …”
Section: Does the Timing Of Implant Placement And Loading Influence B...mentioning
confidence: 99%